Faktor-faktor yang Mempengaruhi Kinerja Perguruan Tinggi - Setiadi, Yusuf; Indrabudiman, Amir (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research aims to test and analyze the effect of Internal Control and Use of Information Technology on Higher Education Performance with Good University Governance as an Intervening Variable. The research methodology used in this research is quantitative. The population in this study were all officials, lecturers and employees at Ichsan Satya University. The sampling technique in this research used simple random sampling with a sample of 83 respondents who met the sample criteria. Data analysis for hypothesis testing uses path analysis through the SmartPLS Program. The results of this research show that internal control has a significantly positive effect on good university governance, the use of information technology has a significantly positive effect on good university governance, internal control has a significantly positive effect on higher education performance, the use of information technology has a significant positive effect on higher education performance, and good university governance significantly has a positive effect on higher education performance.